Rencana Desain Gale-galean di SD Negeri 29 Dangin Puri Denpasar - Arswendo, Galih; Semarajaya, Cokorda Gede Alit; Astawa, I Nyoman Gede (Jurnal Arsitektur Lansekap, 2024)
Playing is the main things for children study. It needs to be inserted by moral values and local culture so that can be delivered and well preserve. Indonesia has aware of importance from playing and built some playing space such as children playground in green space and school which apply a concept of SRA (Sekolah Ramah Anak). inside SRA one importance component is children playground. One of children games/dolanan in Indonesia is gale-galean. Inside gale-galean contains every aspect in outdoor game which stimulate physique, social, cognitive, and emotional development of children. The purpose of this Research is to design gale-galean which located at SD 29 Dangin Puri. Research method has been used was qualitative descriptive which contains 4 systematic element such as: preparation, inventory, analysis, and synthesis. The result of this research is design plan of gale-galean in SD 29 Dangin Puri front yard which use colour dan shape as lines and implement the concept of mandala. Beside that this research consider six criteria in children playground planning. Which is safety, health, comfort, convenience, security, and beauty. This research can be used for preserve gale-galean and beneficial for children grow development.